Time trends of physical activity for leisure and transportation in the Brazilian adult population: results from Vigitel, 2010-2019 - Alessandra de Carvalho Bastone; Bruno de Souza Moreira; Karina Simone de Souza Vasconcelos; Amanda Silva Magalhães; Débora Moraes Coelho; Juliana Ilídio da Silva; Vanessa Moraes Bezerra; Adalberto Aparecido dos Santos Lopes; Amélia Augusta de Lima Friche; Waleska Teixeira Caiaffa; Amanda Cristina de Souza Andrade (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This time-series study examined a 10-year historical series of the physical activity prevalence for leisure and transportation in the Brazilian adult population. Information from 512,969 adults interviewed from the Vigitel between 2010 and 2019 was analyzed. Individuals who reported practicing at least 150 minutes/week of moderate-intensity physical activity or at least 75 minutes/week of vigorous-intensity physical activity were considered active during leisure time. Individuals who reported walking or cycling to/from work, course, or school at least 30 minutes/day, equivalent to at least 150 minutes/week of moderate-intensity physical activity, were considered active during transportation. The prevalence of physical activity for leisure and transportation was calculated annually and stratified by sex, age group, schooling, and race/skin color. The segmented regression model was applied to analyze the time series. Annual percent change and average annual percent change were calculated. Over time, the prevalence of physical activity for leisure increased, and the prevalence of physical activity for transportation decreased. The highest prevalence of physical activity for leisure was observed among males, young individuals, and those with high education. Older adults, those with high education, and white people presented the lowest prevalence of active transport. Policymakers should propose strategies that encourage and facilitate physical activity for leisure in women, individuals aged ≥ 35 years, and those with less education (< 12 years), and physical activity for transportation among older adults (≥ 60 years), those with high education (≥ 12 years), and white people.